Desmoid-Type Fibromatosis of the Thorax: CT, MRI, and FDG PET Characteristics in a Large Series From a Tertiary Referral Center. Issue 38 (September 2015) - Xu, Hai; Koo, Hyun Jung; Lim, Soyeoun; Lee, Jae Wook; Lee, Han Na; Kim, Dong Kwan; Song, Joon Seon; Kim, Mi Young
Abstract : Abstract: The purpose of this study was to describe the radiologic findings of computed tomography (CT), magnetic resonance (MR) imaging, and 18 F-fluorodeoxy glucose positron emission tomography (FDG PET) in desmoid-type fibromatosis of the thorax. We retrospectively evaluated 47 consecutive patients with pathologically proven desmoid-type fibromatosis from January 2005 to March 2015. Patients underwent CT (n = 36) and/or MR (n = 32), and 13 patients also underwent FDG PET. Based on CT and MR, the sizes, locations, margins, contours, presence of surrounding fat, extra-compartment extension, bone involvement, and neurovascular involvement of the tumors were recorded. The attenuation, signal intensity, enhancement pattern, and presence of internal low signal band or signal void of the tumors were evaluated. Initial image findings were then compared between 2 groups of tumors: group 1 with recurrence or progression, and group 2 with no recurrence or stable without treatment. Median age at diagnosis of the tumors was 45 years, range 4 to 96, female-to-male ratio 1.8. Median tumor long diameter was 65 mm (range, 22–126 mm). The most common locations were chest wall (42.6%), followed by supraclavicular area, shoulder or axillary area, and mediastinum. The tumors had well-defined margins (83.0%), lobulated in contours (66.0%) surrounding fat (63.8%), extra-compartment extensions (42.6%), bone involvements (42.6%), and neurovascular involvements (27.7%). On CT, tumors had low attenuation (60.0%) with mild enhancement (median 24 HU, range 0–52). On MR, they showed iso-signal intensity (SI) (96.9%) on T1-weighted images (WI), and high SI (90.6%) on T2WI images, with strong (87.5%) and heterogeneous (96.9%) enhancement. Internal low signal bands (84.4%) and signal voids (68.8%) were noted. The median value of maxSUV was 3.1 (range, 2.0–7.3). In group 1 (n = 19, 40.4%), 13 patients suffered recurrence and 6 experienced progression. Group 2 (n = 28, 59.6%) consisted of 21 patients with no recurrence and 7 stable patients receiving no treatment. Partially ill-defined margins (OR, 0.167; 95% CI 0.029–0.943; P  = 0.043) was the independent predictor for recurrence or progression of tumor. Knowledge of the radiological findings in desmoid-type fibromatosis on CT, MR, and FDG PET may help to improve diagnosis. Tumors with partially ill-defined margins have a tendency to recur or progress.